How the family deals with the child’s learning difficulty in the face of his/her poor school performance? (Research, Society and Development, 2019)
This article aims to study takes as its object the family ties of children with poor academic performance by adopting a relational perspective, which enables the observation of the family as a subject that is likely to establish meaningful relationships among its members. In order to analyze how the family deals with the child’s learning difficulty in the face of his/her poor school performance, a case study was performed in a private school located in a lower-middle-class community in the city of Salvador, whose project was submitted and approved by the Committee of Ethics in Research. Three children took part in the study; two female students, at the age of seven and eight years, who study at the Second Grade of Elementary School, and one male student, at the age of seven, studying at the First Grade of ES; along with their parents. From the basic question, concerning the way parents deal with their children’s difficulty of learning, two procedures were held: the assessment of the children’s learning, using instruments from Visca’s convergent perspective and, then, the analysis of the parent-child interaction, with instruments from the systems theory of the family (collaborative game and genogram). It was found that the children express family bonds characteristic of dependence; that the parental educative practices are conveyed through an authoritarian model with greater control, imposed rules, little support for the child, a lot of demand and lack of affection; that the strategies used by the parents to guide their children’s behavior are characterized by the direct use of force, including physical punishment or the use of intimidation; ultimately, it was found that the present methods for teaching and learning restrict the development of learning because they reduce the child's spaces of choice. In addition, the research demonstrates the quality of the school, the low parental academic education and living in a violent neighborhood as factors that may interfere with learning difficulty and that, therefore, have to be better investigated in future studies.